Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.7 Radical Expressions - R.7 Exercises - Page 75: 57



Work Step by Step

Note that $(-2)^4=16$ and $16=2^4$. Thus, the given expression is equivalent to: $=\sqrt[3]{2^4(16)(2^8)} \\=\sqrt[3]{2^4\cdot2^4\cdot2^8}$ Use the rule $a^m\cdot a^n = a^{m+n}$ to obtain: $=\sqrt[3]{2^{4+4+8}} \\=\sqrt[3]{2^{16}}$ Factor the radicand so that one factor is a perfect cube to obtain: $=\sqrt[3]{(2^{15})(2)} \\=\sqrt[3]{(2^5)^3(2)}$ Bring out the cube root of the perfect cube factor to obtain: $=2^5\sqrt[3]{2} \\=\color{blue}{32\sqrt[3]{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.